Recidivism Guidance Model from an Islamic Education Perspective at Ternate Penitentiary, North Maluku - Amrudin Yakseb; St. Wardah Hanafie Das; Raya Mangsi; Abdul Halik (Lembaga Bale Literasi, 2025)
The phenomenon of recidivism in correctional institutions remains a challenge in the Indonesian correctional system, particularly in North Maluku, despite the implementation of various correctional programs. This study aims to describe the conditions of correctional institutions for recidivists, understand inmates' perspectives on correctional institutions, and develop an effective Islamic Education-based correctional institution model. The study used a descriptive qualitative approach with a phenomenological paradigm focusing on the experiences and perceptions of recidivists in the Class IIA Ternate Penitentiary. Data were collected through observation, structured interviews, and documentation, then analyzed thematically using triangulation techniques to ensure credibility, transferability, dependability, and confirmability of the data. The results show that although the prison provides educational and skills programs, recidivists still experience difficulties in internalizing moral values. The implementation of non-formal Islamic education, such as the Al-Qur'an Education Park (TPQ) and the Majelis Taklim (Islamic study group), has been proven to instill deep spiritual and moral awareness, thereby increasing recidivists' motivation to avoid repeating criminal offenses. These findings provide important implications for the development of a holistic, integrative, and Islamic-values-based development model to reduce recidivism rates in prisons, and serve as a guideline for other correctional institutions in Indonesia.